Fifteen Percent Thermal Burn Injury Developing Severe Acute Respiratory Distress Syndrome - Rupak Chatterjee; Debanjan Mandal; Arnab Mondal; Rupnarayan Bhattacharya; Shatavisa Mukherjee (Journal of Association of Pulmonologist of Tamil Nadu)
Although many medical and surgical illnesses are implicated for development of acute respiratory distress syndrome (ARDS), few diseases contribute predominantly as etiology. Pneumonia and sepsis are the most common causes followed in incidence by aspiration of gastric contents, trauma, multiple transfusions, and drug overdose. Here, we report a case of 15% total body surface area 2nd-degree thermal burn injury developing severe ARDS, which was managed successfully. Apart from mechanical ventilation, aggressive attempts to reduce left atrial filling pressures with fluid restriction and diuretics constitute an important aspect of ARDS management.